Tinjauan Hukum Perdata Terhadap Pemblokiran Rekening Tidak Aktif oleh PPATK dalam Perspektif Perlindungan Pemilik Rekening - Sulaeman; Fardhan Safitra; Andi Wahyuddin Nur; Febriansa Ade Saputra (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
Research into the blocking of dormant accounts by the Financial Transaction Reports and Analysis Center (PPATK) raises legal issues related to the protection of account holders' civil rights. This study aims to analyze the legal basis for PPATK's authority, the status of customers' civil rights, and the forms of legal protection that can be pursued. The research method used is normative juridical with a statutory and conceptual approach, using primary and secondary legal materials. The results of the study indicate that PPATK's authority to request a temporary suspension of transactions has a legal basis in Article 44 paragraph (1) letter i of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering. From a civil law perspective, the relationship between a bank and a customer is a contractual relationship that gives rise to rights and obligations, so that funds in the account remain the property of the customer. Legal protection for account holders is provided preventively through the principles of prudence and transparency, and repressively through complaint mechanisms to the bank, the Financial Services Authority, dispute resolution through alternative institutions, and civil lawsuits. The implications of this study emphasize the importance of a balance between state authority and the protection of customers' civil rights.